Factors During Pregnancy, Delivery and Birth Affecting Global Quality of Life of the Adult Child at Long-term Follow-up. Results from the Prospective Copenhagen Perinatal Birth Cohort 1959-61. (2005) - Ventegodt, Søren; Flensborg-Madsen, Trine; Andersen, Niels Jørgen; Merrick, Joav
Abstract : This paper presents a prospective cohort study, where we explore associations between pregnancy, delivery and the global quality of life (QOL) of the adult child 31-33 years later. The data is from the Copenhagen Perinatal Birth Cohort 1959-61 using two sets of questionnaires send to 7, 222 persons: one filled out by physicians during pregnancy and delivery, while the follow-up questionnaire was completed by the adult children 31-33 years later. The main outcome measures were objective factors describing pregnancy and delivery along with global quality of life, including: Well-being, life satisfaction, happiness, fulfilment of needs, experience of life's temporal and spatial domains, expression of life's potentials and objective measures. Results showed two main factors in pregnancy that seemed to be associated with a reduced quality of life for the child 31-33 years later: the mother's smoking habits and the mother's medication–especially painkillers and different psychopharmacological drugs with the association being most prevalent early in pregnancy. Considering what can and do go wrong during the various stages of labour and delivery and considering how few connections we found between the factors examined and the later global QOL, it seems that the child is remarkably resilient to external influences during pregnancy and delivery concerned with global QOL, as an adult.